2018
DOI: 10.1016/j.exphem.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

A thalidomide–hydroxyurea hybrid increases HbF production in sickle cell mice and reduces the release of proinflammatory cytokines in cultured monocytes

Abstract: Fetal hemoglobin (HbF) induction by hydroxyurea (HU) therapy is associated with decreased morbidity and mortality in sickle cell anemia (SCA) patients, but not all patients respond to or tolerate HU. This provides a rationale for developing novel HbF inducers to treat SCA. Thalidomide analogs have the ability to induce HbF production while inhibiting the release of tumor necrosis factor-alpha. Molecular hybridization of HU and thalidomide was used to synthesize 3- (1,3-dioxoisoindolin-2-yl) benzyl nitrate (com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
1
6
0
1
Order By: Relevance
“…One promising approach for treating SCD is to induce HbF, which does not polymerize, thus preventing hemoglobin polymerization (Sankaran, 2011;Ware et al, 2017). Chelucci et al (2019) promising SCD treatment (Lanaro et al, 2018). Melo et al (2018) reported seven new phthalimide-furoxan conjugates (157-163) (Figure 13), and all the compounds were assessed for their antiplatelet properties.…”
Section: Phthalimides As Fetal Hemoglobin (Hbf) Inducersmentioning
confidence: 99%
See 2 more Smart Citations
“…One promising approach for treating SCD is to induce HbF, which does not polymerize, thus preventing hemoglobin polymerization (Sankaran, 2011;Ware et al, 2017). Chelucci et al (2019) promising SCD treatment (Lanaro et al, 2018). Melo et al (2018) reported seven new phthalimide-furoxan conjugates (157-163) (Figure 13), and all the compounds were assessed for their antiplatelet properties.…”
Section: Phthalimides As Fetal Hemoglobin (Hbf) Inducersmentioning
confidence: 99%
“…In terms of TNF‐α inhibition, compounds 148 and 156 demonstrated the highest inhibition values (Chelucci et al, 2019). Lanaro et al (2018) reported on a phthalimide‐based analog containing the hydroxyurea moiety ( 146 ) and its effects on HbF production and proinflammatory profiles in sickle cell animal models (Figure 12). Compound 146 increased HbF protein levels by 53% compared to the vehicle and exhibited anti‐inflammatory properties by reducing the production of inflammatory cytokines in monocyte cultures from SCA mice.…”
Section: Phthalimides As Fetal Hemoglobin (Hbf) Inducersmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, metformin, a FOXO3 inducer, has been shown to increase HbF production in erythroid cells in vitro , and is now being tested in patients with SCD (NCT02981329). Other promising HbF reactivating agents currently in preclinical studies include recombinant SIRT1 64 , a hydroxyurea-thalidomide hybrid, 65 resveratrol, 66 and dimethyl fumarate. 67…”
Section: [H1] Developing New Scd Therapiesmentioning
confidence: 99%
“…In vitro and in vivo experiments showed that Lapdesf-4c did not exhibit mutagenic and genotoxic effects [9]. Lapdesf-4c also reversed the priapism in sickle transgenic murine models displaying low NO bioavailability after 3-week treatment by inducing phosphodiesterase-5 (PDE-5) expression and reducing protein expression of ROS markers [8,10]. Although such activities suggested a protective profile of Lapdesf-4c in the ED, there is no investigation of those vascular effects.…”
Section: Introductionmentioning
confidence: 99%